Human Immunodeficiency Virus Type 1 Vectors Efficiently Transduce Human Hematopoietic Stem Cells - Sutton, Richard E. (American Society for Microbiology, 1998)
Lentiviruses are potentially advantageous compared to oncoretroviruses as gene transfer agents because they can infect nondividing cells. We demonstrate here that human immunodeficiency virus type 1 (HIV-1)-based vectors were highly efficient in transducing purified human hematopoietic stem cells. Transduction rates, measured by marker gene expression or by PCR of the integrated provirus, exceeded 50%, and transduction appeared to be independent of mitosis. Derivatives of HIV-1 were constructed to optimize the vector, and a deletion of most of Vif and Vpr was required to ensure the long-term persistence of transduced cells with relatively stable expression of the marker gene product. These results extend the utility of this lentivirus vector system.